Minimalist Art and the Iconization of Trees in Waiting for Godot - Irianto, Adhy Pratama; Timmerman, Benny Yohanes; Saleh, Sukmawati (Postgraduate Program of Institut Seni Budaya Indonesia Bandung, 2024)
The minimization of performance art is aimed at presenting human darkness and innocence in a philosophical interpretation. This is what Samuel Beckett presented in his 1953 performance Waiting for Godot. Art minimization makes the number of props less, but is able to visualize the desired thematic of the script. This minimalism, which is supposed to display simplicity, becomes more “luxurious” due to the presence of iconic things from absurd performances. In the midst of the minimalist, gloomy, and arid decorations in Waiting for Godot, the tree becomes the center of attention. This tree becomes something very iconic and will strongly remind the audience of the show. The process of something becoming iconic is called iconization, which is a “deliberate” process. Beckett allegedly deliberately iconizes the tree, with a number of realities in the text (textual) and the reality of the performance (atmospheric). This iconization and minimization is intended to make the performance more basic and simple, less philosophical and metaphysical. This article is the result of an analysis of several texts written by Samuel Beckett.